Non-dominant leg joints bear greater loading during balance beam walking in 4-year-old children - Pan, Jintao; Xu, Zihang; Hu, Xue; Zhu, Weixin; Yang, Qining; Ren, Xiping (Frontiers in Sports and Active Living, 2025)
BackgroundDynamic balance is a critical foundation for the development of motor skills in early childhood. Functional tasks such as beam walking pose a significant challenge to the frontal plane stability of preschool children. However, the mechanisms by which young children regulate hip, knee, and ankle joint loading under such conditions remain unclear. Therefore, this study aimed to explore the regulatory strategies of lower limb joint reaction forces during beam walking in 4-year-old children.MethodsFourteen healthy 4-year-old children participated in overground walking (OGW) and balance beam walking (BBW). A markerless motion capture system, OpenCap, was used to collect kinematic data. Joint reaction forces in the frontal plane for the dominant and non-dominant at the hip, knee, and ankle were computed using OpenSim. One-dimensional time series parameters of joint reaction forces were used to assess loading characteristics between OGW and BBW.ResultsUnder BBW, the medial reaction force at the non-dominant hip joint significantly increased during multiple phases of the gait cycle, and the lateral force at the non-dominant knee joint decreased during the swing phase, with slower medial-to-lateral transitions.ConclusionIn functional walking tasks, asymmetry in lower limb joint loading between the dominant and non-dominant legs may serve as a sensitive indicator for assessing the neuromuscular development and gait control strategies in preschool children.